PEI-modified core-shell/bead-like amino silica enhanced poly (vinyl alcohol)/chitosan for diclofenac sodium efficient adsorption. (1st February 2020) - Lu, Yuqing; Fan, Lihong; Yang, Li-Ye; Huang, Fangfang; Ouyang, Xiao-kun
Graphical abstract: Highlights: A core shell/bead-like PVA/CS/SAP@PEI was fabricated for diclofenac sodium removal. Adsorbent exhibits excellent adsorption capacity ascribed to the sufficient amino. Mechanical stability of the beads is guaranteed by nanofillers and PEI coating. It is easily separated after adsorption in aqueous solution and is recyclable. Abstract: Residual diclofenac sodium (DS) in water is a potential hazard. The electrostatic attraction between amino group of adsorbents and carboxyl group of DS under acidic conditions can effectively remove DS from water. Herein, a novel core–shell adsorbent of poly(vinyl alcohol)/chitosan/amino-grafted silica@polyethylenimine (PVA/CS/SAP@PEI) gel bead was prepared to efficiently uptake DS from wastewater. In this study, the gel bead was characterized using FTIR, XPS, SEM, EDS, and 13 C NMR. The experimental data shows that there is a strong correlation between adsorption capacity. The adsorption data fitted well with the Freundlich isotherm model and the pseudo-second-order model. The results of thermodynamics show that the adsorption process is spontaneous, endothermic, and increases entropy. The maximum adsorption capacity for DS was calculated as 493.81 mg/g at pH 5 (308 K). The adsorbent still exhibited excellent adsorption capacity after recycling five times, showing it has excellent potential for practical applications.